1999
DOI: 10.1002/hep.510290533
|View full text |Cite
|
Sign up to set email alerts
|

Deranged blood coagulation equilibrium as a factor of massive liver necrosis following endotoxin administration in partially hepatectomized rats

Abstract: Activated Kupffer cells provoke massive liver necrosis after endotoxin stimulation through microcirculatory disturbance caused by sinusoidal fibrin deposition in rats undergoing 70% hepatectomy. In these rats, serum activities of purine nucleoside phosphorylase (PNP) and alanine transaminase (ALT) were increased at 1 and 5 hours, respectively, following endotoxin administration. When 70% resected liver was perfused with Dulbecco's modified Eagle medium (DMEM) containing heat-inactivated fetal calf serum, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Baseline and stimulated serum paraoxonase activities are decreased in chronic hepatitis and liver cirrhosis (10 ). In rats, PNP activity was demonstrated to increase 5 h after the administration of endotoxin (11 ).…”
Section: Proteomics Resultsmentioning
confidence: 97%
“…Baseline and stimulated serum paraoxonase activities are decreased in chronic hepatitis and liver cirrhosis (10 ). In rats, PNP activity was demonstrated to increase 5 h after the administration of endotoxin (11 ).…”
Section: Proteomics Resultsmentioning
confidence: 97%
“…TF is involved in the development of hepatocellular injury in other rodent models, such as hepatic ischemia-reperfusion and endotoxemia/partial hepatectomy. [26][27][28] Although a causal role for TF in human APAP-induced liver injury has not been established, there is some evidence that TF mediates coagulation system activation in cases of APAP overdose. For example, the concentrations of several coagulation factors (II, V, VII, and X) were reduced in patients with acute liver injury from APAP overdose, and this was interpreted to reflect TF-initiated coagulation and consumption of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that LPS up-regulates the expression of tissue factor on sinusoidal endothelial cells of the liver. 25,26 We also previously showed that LPS up-regulates VEGF expression by macrophages in vitro. 27 Furthermore, since drugs such as BU, CY, and CsA are metabolized and/or activated by hepatocytes, the endothelium of sinusoids and hepatic veins are directly exposed to these agents at high concentrations, enough to injure the endothelium.…”
Section: Discussionmentioning
confidence: 87%